If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + -15 = -6x Reorder the terms: -15 + -9x = -6x Solving -15 + -9x = -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -15 + -9x + 6x = -6x + 6x Combine like terms: -9x + 6x = -3x -15 + -3x = -6x + 6x Combine like terms: -6x + 6x = 0 -15 + -3x = 0 Add '15' to each side of the equation. -15 + 15 + -3x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + -3x = 0 + 15 -3x = 0 + 15 Combine like terms: 0 + 15 = 15 -3x = 15 Divide each side by '-3'. x = -5 Simplifying x = -5
| 6=-0.026x^2+0.526x+5 | | -2x+8=-5x+8 | | 5d=2dx-18 | | 8t^2-14t+3= | | 100=x+x+11 | | 3B+2.1=19.2 | | 8(x-4)=40 | | 4(x+4)+2=2 | | 5y-10=2x | | 154=x+2x+x+14 | | 6(5*40-4)-3(10*40+2)=10 | | (9y+28)+(x+5)=180 | | 4.6=1.2+1.7x | | 2.03=a/740 | | ln(x)+ln(x+6)=3 | | Logx=235 | | 6/7=-2x-8/7 | | 5(x-2)-2x=8 | | 5x^2-9=7x | | x^2+3x-1.5=0 | | ln(x+4)-ln(x-2)=lnx | | 1/4(x-7)== | | 2x+2x+5x-2-2-17=180 | | 9x+5=5-(2x-8) | | -12/-12 | | 85*40-(5-9*40)*9=3*40-5 | | (9x^2+6x+3)(5x+2)= | | 24x+54=180 | | 24x=54 | | -12/5/-6 | | 5x+2y-5z=-34 | | 5(a+3)-9=-4(9-6)+1 |